2017
DOI: 10.1002/jcc.24875
|View full text |Cite
|
Sign up to set email alerts
|

An interaction energy driven biased sampling technique: A faster route to ionization spectra in condensed phase

Abstract: We introduce a computationally efficient approach for calculating spectroscopic properties, such as ionization energies (IEs) in the condensed phase. Discrete quantum mechanical/molecular mechanical (QM/MM) approaches for spectroscopic properties in a dynamic system, such as aqueous solution, need a large sample space to obtain converged estimates, especially for the cases where particle (electron) number is not conserved, such as IEs or electron affinities (EAs). We devise a biased sampling technique based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 96 publications
4
12
0
Order By: Relevance
“…We have noticed that solvatochromic shift in VIE (DVIE) is directly proportional to DE int . [70] In the case of guanine, we have noticed similar correlation ( Figure S2(a) in Supporting Information). It is important to mention here that the computation of DE int for a configuration is computationally inexpensive when compared to a hybrid QM/ EFP calculation to predict DVIE.…”
Section: Biased Sampling For Faster Convergencesupporting
confidence: 70%
See 1 more Smart Citation
“…We have noticed that solvatochromic shift in VIE (DVIE) is directly proportional to DE int . [70] In the case of guanine, we have noticed similar correlation ( Figure S2(a) in Supporting Information). It is important to mention here that the computation of DE int for a configuration is computationally inexpensive when compared to a hybrid QM/ EFP calculation to predict DVIE.…”
Section: Biased Sampling For Faster Convergencesupporting
confidence: 70%
“…The difference in interaction energy can be expressed as, ΔEint=isolutejsolventQi,esqjrij isolutejsolventQi,gsqjrij, where Qi,es and Qi,gs refer to the charge of the i th atom of the solute (QM region) in its excited and ground state, respectively, and q j refers to the charge of the j th atom of the solvent (MM region) and r ij is the distance between these points. We have noticed that solvatochromic shift in VIE (ΔVIE) is directly proportional to Δ E int . In the case of guanine, we have noticed similar correlation (Figure S2(a) in Supporting Information).…”
Section: Computational Detailssupporting
confidence: 68%
“…To have a quantitative understanding of the dependence of VDE values on the number of water molecules, we have checked the convergence of the VDE with respect to the number of solvation shells. We have first prescreened 42 snapshots using energy‐based criteria . We have chosen only those snapshots whose VDE values are within 0.65 eV of the average VDE of the original 400 snapshots.…”
Section: Resultsmentioning
confidence: 99%
“…The microsolvation studies on thymine always show a red-shift in the IP values. [29,41] A careful look at the mono-hydrated and di-hydrated structures shows that the isomers for which the water molecules are exclusively hydrogen bonded to thymine (1B and 2B) show a red-shift of the second IP values. However, the overall trend in microsolvation studies on the AT base pair shows that the presence of one or two water molecules cannot reproduce the behavior of the bulk environment.…”
Section: Ionization Energymentioning
confidence: 99%
“…[11,21] However, the efficiency of the EFP-EOM-CCSD method is limited by the expensive EOM-CCSD calculation on the solute, which can become a bottleneck for base pairs and larger DNA fragments, especially when one needs to run hundreds of snapshots to perform dynamic averaging of the calculation over multiple snapshots. Ghosh and co-workers have recently reported a biased sampling technique, [29] which can reduce the number of snapshots required to get converged IP values. However, to the best of our knowledge, no explicit solvation-based studies have been reported to investigate the effect of bulk solvation on the IP values of base pairs.…”
mentioning
confidence: 99%